Energy and nutrient intake in Mexican children 1 to 4 years old: results from the Mexican National Health and Nutrition Survey 2006 Consumo de energía y nutrimentos en niños mexicanos de 1 a 4 años de edad: resultados de la Encuesta Nacional de Salud y Nutrición 2006 - Verónica Mundo-Rosas; Sonia Rodríguez-Ramírez; Teresa Shamah-Levy (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE: To document the energy and nutrient intake of Mexican preschool children using data from the Mexican National Health and Nutrition Survey 2006 (ENSANUT 2006). MATERIAL AND METHODS: Dietary data from 3 552 children less than 5 years old collected through a semi-quantitative food frequency questionnaire were analyzed. Energy and nutrient daily intakes and adequacies were calculated. Comparisons were made by geographic region, residence locality, and socioeconomic status. RESULTS: The Mexico City region showed the highest energy (103.2%), carbohydrate (109.9%), and fat (110.1%) adequacies. The highest proportion of preschoolers with energy and micronutrients inadequacy (adequacy < 100%) was observed in children of indigenous ethnicity, low socioeconomic status, living in rural localities, and in the south region. CONCLUSIONS: This information may help as an indicator of food availability and access in different population strata and as a tool to focus interventions on those who may better benefit from food assistance programs. OBJETIVO: Documentar el consumo de energía y nutrimentos en niños mexicanos menores de cinco años, a partir de datos de la Encuesta Nacional de Salud y Nutrición 2006 (ENSANUT 2006), realizada en México en 2006. MMATERIAL Y MÉTODOS: Se analizó información de un cuestionario semicuantitativo de frecuencia de consumo de alimentos de 3552 niños. Se calcularon consumos y adecuaciones diarias de energía y nutrimentos, comparando por región geográfica, tipo de localidad y nivel socioeconómico. RESULTADOS: La región Ciudad de México presentó la adecuación más alta de energía (103.2%), carbohidratos (109.9%) y grasa (110.1%). Las proporciones más altas de inadecuación (adecuación < 100%) en energía y micronutrimentos se observaron en las localidades rurales, indígenas, región sur y nivel socioeconómico bajo. CONCLUSIONES: Esta información es un indicador de la disponibilidad y acceso a los alimentos de diferentes estratos de la población y una herramienta para focalizar a los beneficiarios de programas de asistencia alimentaria.